Training with TRX to increase speed in youth baseball players in Matanzas - Alexis García-Ponce de León; José Enrique Carreño-Vega; Osmani Evelio Mercadet-Portillo (Universidad de Guantánamo, 2019)
Suspension training (TRX) has become one of the most widely used functional training systems due to its effectiveness and versatility. In this research, a functional training with TRX is designed to increase the speed in the home-first base run of the youth baseball players of Matanzas. It is obtained, that this training program planned in fifteen weeks, with three weekly frequencies, achieves significant changes in the times of the home-first race, with a 4.37% increase, being the gardeners and the left-handed players more effectively.